Einfluss des Klimawandels auf die deutsche Energieversorgung - Hubertus Bardt; Hendrik Biebeler; Heide Haas (Wirtschaftsdienst, 2013)
Die Energieversorgung in Deutschland steht einerseits vor der Aufgabe, die Energiewende mit einem sicher funktionierenden Energie- und Stromversorgungssystem zu meistern. Andererseits sind die Energieversorgungsunternehmen auch selbst dem Klimawandel ausgesetzt. Der im Institut der deutschen Wirtschaft entwickelte Klimarisiko-Indikator gibt Aufschluss über die Risiken der einzelnen Energieträger vor und nach der Energiewende. – – German energy supply faces a fundamental and long-term change. By the middle of the century, greenhouse gas emissions will have been greatly reduced and the global climate will start to change in a visible manner. In order to determine and to quantify the physical impacts of climate change on energy supply, a climate risk indicator for the energy industry based on a series of expert interviews has been developed. Climate change-induced risks will slightly outweigh the opportunities. The restructuring of the energy system has only minor effects, because the risks inherent to non-renewable energies, in particular those related to cooling water, are replaced by new risks, especially deriving from the use of biomass.
Keywords: Q20; Q48; Q54; 330; Klimaveränderung; Förderung regenerativer Energien; Energieversorgung; Elektrizitätswirtschaft; Deutschland